Neonatal supraventricular extrasystole as early clinical debut of cardiac rhabdomyoma - Roger Esmel-Vilomara; Amparo Castellote; Luz Santana; Dimpna Calila Albert (Wolters Kluwer Medknow Publications, 2018)
We are reporting the case of a newborn with a diagnosis of frequent supraventricular extrasystoles, up to 25% of beats at Holter monitoring, and partial response to beta-blockers. Initial echocardiographic studies were normal until the identification of a right atrial mass at 4 months of life. Given the progressive growth of the mass and the suspicion of myxoma or thrombus in the magnetic resonance study, surgical resection of the tumor was performed. The surgical specimen was histologically diagnostic of rhabdomyoma. Currently, the patient remains asymptomatic after a 6-year follow-up period. A single rhabdomyoma is described, located in an atypical situation, near the crista terminalis, and diagnosed from frequent extrasystoles which appeared before the echocardiographic resolution was able to identify it. Magnetic resonance showed nondiagnostic tissue enhancement characteristics.